Antifungal activity of essential oils obtained from roots and rhizomes of Kaempferia galanga Linn., Alpinia galanga (Linn.) and Alpinia calcarata Roscoe. against Rhizoctonia solani - ARCHANA P. RAINA, LAKSHMAN PRASAD*, V.S. Rana and (Indian Phytopathology, 2016)
Rhizoctonia solani can infect plants belonging to > 32 families and 188 genera. This pathogen also causes major yield loss worldwide in many crops like: rice, green gram, cowpea, gram and groundnut, soybean, maize, jowar, wheat and bajra etc. Essential oils are natural, volatile complex terpenoid compounds characterized by a strong and specific odour. These secondary metabolites are formed by aromatic plants and are obtained by hydro-distillation technique. The essential oils were isolated from roots and rhizomes of three plants belonging to family Zingiberaceae. In vitro experiments using essential oils isolated from these plants were found effective against Rhizoctonia solani. The root oil of Alpinia galanga, showed best antifungal efficacy at 500 ppm in inhibiting 40% growth and development in different stages of life cycle of R. solani. However, among all three essential oils tested, the A. galanga root oil was found most effective than rhizome oils from Kaempferia galanga and A. galanga. Results suggested the possible exploitation of these oils as potential fungal control agents of botanical source. Fungicidal formulations can be prepared using these oils for agricultural applications.